Methyl Salicylate Lactoside Protects Neurons Ameliorating Cognitive Disorder Through Inhibiting Amyloid Beta-Induced Neuroinflammatory Response in Alzheimer’s Disease - Li, Jinze; Ma, Xiaowei; Wang, Yu; Chen, Chengjuan; Hu, Min; Wang, Linlin; Fu, Junmin; Shi, Gaona; Zhang, Dongming; Zhang, Tiantai (Frontiers in Aging Neuroscience, 2018)
Neuroinflammatory reactions mediated by microglia and astrocytes have been shown to play a key role in early progression of Alzheimer’s disease (AD). Increased evidences have demonstrated that neurons exacerbate local inflammatory reactions by producing inflammatory mediators and act as an important participant in the pathogenesis of AD. Methyl salicylate lactoside (MSL) is an isolated natural product that is part of a class of novel non-steroidal anti-inflammatory drugs (NSAID). In our previous studies, we demonstrated that MSL exhibited therapeutic effects on arthritis-induced mice and suppressed the activation of glial cells. In the current study, we investigated the effects of MSL on cognitive function and neuronal protection induced by amyloid-beta peptides (Aβ) and explored potential underlying mechanisms involved. Amyloid precursor protein (APP) and presenilin 1 (PS1) double transgenic mice were used to evaluate the effects of MSL through behavioral testing and neuronal degenerative changes. In addition, copper-injured APP Swedish mutation overexpressing SH-SY5Y cells were used to determine the transduction of cyclooxygenase (COX) and mitogen-activated protein kinase (MAPK) pathways. Our results indicated that at an early stage, MSL treatment ameliorated cognitive impairment and neurodegeneration in APP/PS1 mice. Moreover, in an in vitro AD model, MSL treatment protected injured cells by increasing cell viability, improving mitochondrial dysfunction, and decreasing oxidative damage. In addition, MSL inhibited the phosphorylated level of c-Jun N-terminal kinase (JNK) and p38 MAPK, and suppressed the expression of COX-1/2. As a novel NSAIDs and used for the treatment in early stage of AD, MSL clearly demonstrated cognitive preservation by protecting neurons via a pleiotropic anti-inflammatory effect in the context of AD-associated deficits. Therefore, early treatment of anti-inflammatory therapy may be an effective strategy for treating AD.